Technical and Vocational Teacher Education and Training in International and Development Co-Operation : Models, Approaches and Trends - Bünning, Frank, editor 364969; Spöttl, Georg, editor 430028; Stolte, Harry, editor 652677; SpringerLink (Online service) 666 (Singapore : Springer Nature Singapore, 2022)
This book deals with teacher training for vocational education and training. In individual chapters next to the positions of relevant international organizations, donors and development banks, it also covers selected countries in their ways of shaping of Technical Vocational Education and Training and teacher training. The structure of the book aims at two objectives: To outline positions of important stakeholders of the international Technical Vocational Education and Training policies and international cooperation in TVET teacher training. To discuss the current status of Technical Vocational Education and Training and teacher training in selected countries, from developing countries, countries with emerging economies to industrialized countries. The book is meant to create a platform that supports a reference concept within international cooperation for the further development of Technical Vocational Education and Training and teacher training up to a higher quality and performance.